2018
DOI: 10.1021/acs.jmedchem.7b01598
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N-{cis-3-[Methyl(7H-pyrrolo[2,3-d]pyrimidin-4-yl)amino]cyclobutyl}propane-1-sulfonamide (PF-04965842): A Selective JAK1 Clinical Candidate for the Treatment of Autoimmune Diseases

Abstract: Janus kinases (JAKs) are intracellular tyrosine kinases that mediate the signaling of numerous cytokines and growth factors involved in the regulation of immunity, inflammation, and hematopoiesis. As JAK1 pairs with JAK2, JAK3, and TYK2, a JAK1-selective inhibitor would be expected to inhibit many cytokines involved in inflammation and immune function while avoiding inhibition of the JAK2 homodimer regulating erythropoietin and thrombopoietin signaling. Our efforts began with tofacitinib, an oral JAK inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 46 publications
1
91
0
Order By: Relevance
“…A clinical trial, designed to compare upadacitinib with adalimumab and placebo is ongoing (NCT02629159); all told, at least 20 clinical trials are ongoing in arthritis, IBD, and dermatological diseases (Table ). Itacitinib is also a selective JAK1 inhibitor being studied in phase 3 trials in GVHD (NCT03139604, NCT03320642) and malignancies (hematologic and solid tumor), and PF‐ 04965842 is a JAK1 inhibitor being investigated for treatment of psoriasis and atopic dermatitis . GSK2586184 is a selective JAK1 inhibitor studied in IBD, SLE, and psoriasis but a clinical trial is reported to be terminated because of drug interactions with statins (NCT02000453).…”
Section: Next‐generation Selective Jakinibsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial, designed to compare upadacitinib with adalimumab and placebo is ongoing (NCT02629159); all told, at least 20 clinical trials are ongoing in arthritis, IBD, and dermatological diseases (Table ). Itacitinib is also a selective JAK1 inhibitor being studied in phase 3 trials in GVHD (NCT03139604, NCT03320642) and malignancies (hematologic and solid tumor), and PF‐ 04965842 is a JAK1 inhibitor being investigated for treatment of psoriasis and atopic dermatitis . GSK2586184 is a selective JAK1 inhibitor studied in IBD, SLE, and psoriasis but a clinical trial is reported to be terminated because of drug interactions with statins (NCT02000453).…”
Section: Next‐generation Selective Jakinibsmentioning
confidence: 99%
“…inhibitor being studied in phase 3 trials in GVHD (NCT03139604, NCT03320642) and malignancies (hematologic and solid tumor), and PF-04965842 is a JAK1 inhibitor being investigated for treatment of psoriasis and atopic dermatitis. 174,175 GSK2586184 is a selective JAK1 inhibitor studied in IBD, SLE, and psoriasis but a clinical trial is reported to be terminated because of drug interactions with statins (NCT02000453).…”
Section: Jak1 Inhibitorsmentioning
confidence: 99%
“…The aim of this study was to determine the safety and tolerability, as well as pharmacokinetics (PK) and pharmacodynamics (PD), of PF‐04965842, a JAK1‐selective inhibitor , in healthy adult subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The model of human JAK1 was derived from the crystallographic structure deposited in the RCSB PDB databank () [34] with ID codes 6BBU [28]. All the 3D coordinates of crystallographic ligands (i.e., true inhibitors) were retrieved from RCSB PDB databank () [34], while those of Hyp, protohypericin, and protopseudohypericin were retrieved from PubChem database (National Center for Biotechnology Information, ; accessed March 2018) [39].…”
Section: Methodsmentioning
confidence: 99%
“…Representation of the JH1 domain of JAK1. The crystallographic structure (PDB ID 6BBU) [28] is represented in white surface while the co-crystallized ligand is represented in yellow sticks. The protein surface forming the ATP binding site is colored in pale yellow.…”
Section: Figurementioning
confidence: 99%